Pengaruh Opini Going Concern dan Financial Distress Terhadap Auditor Switching Pada Perusahaan Subsektor Transportasi yang Terdaftar di Bursa Efek Indonesia Periode 2018-2022 - Rohim, Abdul; Oktariansyah, Oktariansyah; Rosadian, Aprizal (PPSDP Undergraduate Journal of Educational Sciences, 2025)
This study aims to examine the effect of going concern opinion and financial distress on auditor switching by voluntary companies both partially and simultaneously. This research includes a type of quantitative research with a causal associative method that connects the cause and effect of two or more variables. The population in this study were transportation subsector companies listed on the Indonesia Stock Exchange for the period 2018-2022, totaling 51 companies. The sampling technique in this study used purposive sampling technique so that the companies sampled were 20 companies. The data used is secondary data in the form of financial and annual reports downloaded from the official IDX website, namely www.idx.co.id. The data analysis technique used in this study is descriptive statistical analysis and logistic regression analysis. The test results show that partially going concern opinion has a positive and significant effect on auditor switching, while financial distress has no effect on auditor switching. Simultaneously going concern opinion and financial distress affect auditor switching.